Food Poisoning Caused by Puffer Fish and Ocean Tuna - Ba Le Huy; Hoan Nguyen Xuan; Phong Nguyen Tan; Thanh Le Minh (Food Toxicology: Theory, Practice and Resolve in Vietnam, 2022)
The basic content of chapter 15 is to state the cause of human poisoning by eating poisonous Animal Contains toxic, Noxious. This chapter covers the following topics: 1 - Overview of puffer fish and it’s harmful 2 - Types of puffer fish and its edible parts; 3 - Puffer fish species are poisonous, inedible 4 - Puffer fish toxin 5 - Fire fish poisoning and prevention measures 6 - Prevention measures for possibility by eating fight fish (including: for fishermen; for fish processors; for fish traders; with governments at all levels. 7 - With ocean tuna food poisoning: characteristic, nutritional value. 8 - Tuna toxin poisoning: cause skin itching for people to eat, but not very dangerous